Hormone Signaling and Its Interplay With Development and Defense Responses in Verticillium-Plant Interactions - Dhar, Nikhilesh; Chen, Jie-Yin; Subbarao, Krishna V.; Klosterman, Steven J. (Frontiers in Plant Science, 2020)
Soil-borne plant pathogenic species in the fungal genus Verticillium cause destructive Verticillium wilt disease on economically important crops worldwide. Since R gene-mediated resistance is only effective against race 1 of V. dahliae, fortification of plant basal resistance along with cultural practices are essential to combat Verticillium wilts. Plant hormones involved in cell signaling impact defense responses and development, an understanding of which may provide useful solutions incorporating aspects of basal defense. In this review, we examine the current knowledge of the interplay between plant hormones salicylic acid, jasmonic acid, ethylene, brassinosteroids, cytokinin, gibberellic acid, auxin, and nitric oxide, and the defense responses and signaling pathways that contribute to resistance and susceptibility in Verticillium-host interactions. Though we make connections where possible to non-model systems, the emphasis is placed on Arabidopsis-V. dahliae and V. longisporum interactions since much of the research on this interplay is focused on these systems. An understanding of hormone signaling in Verticillium-host interactions will help determine the molecular basis of Verticillium wilt progression in the host and potentially provide insight on alternative approaches for disease management.